STRATEGI PEMBELAJARAN MUSIK PERKUSI UNTUK PESERTA DIDIK TUNA RUNGU : (Studi Kasus Deaf Percussion SLB Negeri Surakarta) - Rr. Diana Insyafari (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2022)
Percussion music is one of the musical art materials in Surakarta State SLB. Teaching percussion music to Deaf children is difficult because they cannot hear and speak. This research develops a strategy and method of learning percussion music that is easily understood by Deaf children. The strategies used are: 1) Creating Percussion Notation that can be understood by Deaf children, 2) Creating sign language for the basic techniques of playing percussion, 3) Creating lip movements about the basic techniques of percussion playing, 4) Making a summary of the material with sentences that simple that can be understood by Deaf children, 5) Using Kahoot for learning evaluation.